2010
DOI: 10.1590/s1679-62252010005000008
|View full text |Cite
|
Sign up to set email alerts
|

Feeding dynamics of Cichla kelberi Kullander & Ferreira, 2006 introduced into an artificial lake in southeastern Brazil

Abstract: The objective of this study was to characterize the seasonally of the diet of Cichla kelberi in an artificial lake in Leme-SP, determining the food items and their relation to the sex and gonadal maturity of the fish sampled. The diet of C. kelberi presents a dynamic in three different periods: winter months were characterized by low feeding activity and a high concentration of undetermined fish; increase in feeding activity occurred in the spring, with Tilapia sp. being the dominant food item; and a high rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…A diverse diet has been reported in other Amazonian systems, with predominance of fish and low rates of cannibalism (Jepsen et al, 1997;Winemiller, 2001;Montaña et al, 2011). When Cichla is non-native, however, its diet is poor and based on cannibalism, invertebrates and a few non-native fish (Fugi et al, 2008;Capra & Benneman, 2009;Villares Junior & Gomiero, 2010;Santos et al, 2011). In Lajeado reservoir, cannibalism and non-fish resources summed less than 1% of all volume ingested.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A diverse diet has been reported in other Amazonian systems, with predominance of fish and low rates of cannibalism (Jepsen et al, 1997;Winemiller, 2001;Montaña et al, 2011). When Cichla is non-native, however, its diet is poor and based on cannibalism, invertebrates and a few non-native fish (Fugi et al, 2008;Capra & Benneman, 2009;Villares Junior & Gomiero, 2010;Santos et al, 2011). In Lajeado reservoir, cannibalism and non-fish resources summed less than 1% of all volume ingested.…”
Section: Discussionmentioning
confidence: 99%
“…Basic ecological aspects (e.g., feeding, reproduction) have been studied in hydrographic basins where Cichla is nonnative, particularly in the rio Paraná basin (e.g., Fugi et al, 2008;Souza et al, 2008;Gomiero et al, 2009;Vieira et al, 2009;Espínola et al, 2010;Villares Junior & Gomiero, 2010;Luiz et al, 2011;Santos et al, 2011). This information is important to clarify issues related to impact and invasion, but has little significance for the understanding of colonization, dynamics and persistence of native populations in Amazonian reservoirs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it was observed that cannibalism is more accentuated during Cichla's spawning periods and due to scarcity of alternative food items, such as small individuals of small native fish species (Gomiero & Braga, 2004;Villares Junior & Gomiero, 2010). On the other hand, low rates of cannibalism occur in natural environments and in invaded sites mainly due to high availability of prey (Resende et al, 2008;Winemiller et al, 1997;Zaret, 1977).…”
Section: Since Neutral Genetic Diversity Appear Unimportant In Cichlamentioning
confidence: 99%